2018
DOI: 10.46364/njmlm.v6i1.415
|View full text |Cite
|
Sign up to set email alerts
|

Challenges concerning argumentative writing in a second language context

Abstract: The current study is based on parts of the data collected in a quasi-experiment conducted in four English classes of Norwegian upper secondary school students. The purpose of the quasi-experiment was to explore whether a teaching intervention based on systemic functional linguistics and genre-pedagogy would support students in improving their competence in writing argumentative texts in English. The improvement was measured by comparing evaluations of pre-and post-tests. The current study investigates what see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The students' chosen focus areas mirror some of the challenges Norwegian students have when writing English documented in previous research (Horverak, 2016(Horverak, , 2018. They struggle with writing proper paragraphs or structuring texts, and to write in a formal language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The students' chosen focus areas mirror some of the challenges Norwegian students have when writing English documented in previous research (Horverak, 2016(Horverak, , 2018. They struggle with writing proper paragraphs or structuring texts, and to write in a formal language.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there may be different exercises to choose from, teachers and censors have an underlying expectation that the students write a text that complies with the requirements of a five-paragraph essay (Horverak, 2016), and this type of formal writing may be challenging for students. Some of the features Norwegian students struggle with when writing English texts are to get the structure right, to ensure that the argumentation is thorough, to use sources in a sensible way and to adjust the language to purpose and situation (Horverak, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The result of this study corresponds with the previous research. Some studies have reported that students encountered difficulties in the organization in general (e.g., Dang et al, 2020;Horverak, 2018;Ka-kan-dee & Kaur, 2014;Saprina et al, 2021;Saputra et al, 2021;Toan et al, 2020). Moreover, students experienced failure in creating a claim, thesis statement, or their position towards the issue (e.g., Beniche, 2021;Ghanbari & Salari, 2022;Ozfidan & Mitchell, 2020;Peloghitis, 2016;Saprina et al, 2021;Toan et al, 2020;Wingate, 2012).…”
Section: Think Claim Closing and Mostly When I Have To Analyze The So...mentioning
confidence: 99%
“…They observed 12 Indonesian English major student teachers by implementing in-depth interviews and all of them admitted they had insufficient vocabulary. In her study, Horverak (2018) observed 83 Norwegian university students' argumentative essays and found out that the students encountered difficulties in academic vocabulary and adjusting the language to the appropriate level of formality. These studies have confirmed that vocabulary was difficult for the students.…”
Section: Vocabulary Is Difficult I Have Only Some Familiar General Wo...mentioning
confidence: 99%
See 1 more Smart Citation